2015
DOI: 10.1111/scd.12153
|View full text |Cite
|
Sign up to set email alerts
|

An alternate technique of care using silver fluoride followed by stannous fluoride in the management of root caries in aged care

Abstract: An alternate technique of care to prevent, arrest and manage root caries using aqueous silver fluoride followed by stannous fluoride (AgF+SnF2) in aged care is demonstrated by three case studies. With increasing age, the inability to maintain ones own oral care from dementia, illness or frailty and polypharmacy induced salivary gland hypofunction will result in dental caries becoming a progessively greater burden for the elderly. Future generations of elders will live longer and need to maintain many more teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…Figure shows his condition as reported previously in an earlier publication . The patient had a lower overlay denture covering five carious anterior root stumps (Figures a and b).…”
Section: Case Reportmentioning
confidence: 53%
See 4 more Smart Citations
“…Figure shows his condition as reported previously in an earlier publication . The patient had a lower overlay denture covering five carious anterior root stumps (Figures a and b).…”
Section: Case Reportmentioning
confidence: 53%
“…As reported previously, the principal author has found that the higher pH of SDF, presumably due to the presence of ammonia, can cause gingival irritation or a transient chemical burn which may result in resistance to repeated frequent applications of SDF in patients showing challenging behaviors or in the elderly with thin tissue biotype . In contrast, the use of AgF+SnF 2 appears not cause gingival irritation even when applied to all root surfaces over a wide area.…”
Section: Case Reportmentioning
confidence: 62%
See 3 more Smart Citations